Workforce and welfare: Linking child protection staffing levels to recurrence risk - Tonino Esposito; Johanna Caldwell; Martin Chabot; Stéphanie Précourt; Nico Trocmé; Barbara Fallon; Sonia Hélie; John Fluke; Dana Hollinshead (Child Protection and Practice)
Background: Recurrent involvement with a child protection (CP) system may indicate a failure of the system to intervene effectively following an initial CP report. While there are several ecological, socioeconomic, and organizational factors that may influence whether a family experiences recurrence, not much is known about the relationship of CP staffing levels to the likelihood of recurrence. Objective: This study employs data from across geographies of Quebec to explore whether the number of child protection workers responsible for evaluating reported concerns was associated with the likelihood of recurrence. We hypothesized that a higher number of workers would decrease the likelihood of recurrent substantiations during the study period. Participants and setting: Anonymized administrative CP data on first and subsequent substantiated reports were drawn from the Quebec CP system spanning the years 2000–2017. The study sample consisted of 720,681 children who were evaluated for the first time during the study period, of whom 25 % (n = 176,555) experienced a recurring substantiated investigation prior to age 18 or the end of the observation window. Annual levels of evaluation staffing levels for the CP agencies were extracted for the same time period and linked to the administrative dataset. Methods: Using a multilevel model, this study tested whether the number of CP evaluation workers per capita in a family's service delivery area was correlated to the likelihood of recurrent substantiation. Findings: After controlling for geographically measured socioeconomic vulnerability, we found a significant correlation between lower child population staffing levels and an increased likelihood of recurrent substantiation.”. The residual variance was 28.5 % lower for the model including child population staffing levels. Conclusion: Results of the analysis demonstrated a significant role of staffing levels in determining risk of recurrent substantiation in Quebec. More research is needed to understand the mechanisms underlying this relationship to better inform practice and policy improvements.